Causes of Deforestation and Conservation of Madhupur Sal Forest in Tangail Region (Journal of Environmental Science and Natural Resources, 2015)
Over the past few decades deforestation has become the issue of global concern for its rapid reduction of biodiversity. The tropical moist deciduous Sal forest ecosystem of central Bangladesh is currently in a critical situation. Destructive anthropogenic and natural impacts coupled with overexploitation of forest resources have caused severe damage to the forest ecosystem. Due to rubber monoculture, expanding commercial fuel wood plantations & expanding agriculture, illegal cutting, encroachment of forest areas, and illegal poaching of wildlife, the Sal forest is losing biodiversity alarmingly. The study is based on intensive literature survey and tries to explore the overall deforestation situation and conservation practices for Madhupur Sal forest that comprises about 5% of the total forests in Bangladesh. The level of destruction of the natural Sal forest has pushed the forest-dwelling indigenous Garo community into cash crop production, forcing them to move away from their traditional subsistence economy. Now we need to address a joint conservation and improved management plan of the forest resources use. Thus all kinds of military establishments, construction of roads and highways for military purposes should be avoided and a policy of planned industrialization should be adopted to mitigate the adverse effect of industrialization. Findings of the study will help to identify the causes of deforestation and conservation of Madhupur Sal forest and also in other national parks in Bangladesh which ultimately conserve the biodiversity and help to maintain natural balance.DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22105 J. Environ. Sci. & Natural Resources, 6(2): 109-114 2013